Optimasi Fermentasi Anaerob pada Produksi Biogas dari Eceng Gondok dan Kotoran Sapi dengan Response Surface Methodology - Aziz, Ahmad Musonnifin (Program Studi Teknik Kimia, Universitas Pamulang, 2025)
Biogas is a natural gas produced by anaerobic bacteria from processing organic matter and used in energy production. The use of biogas is a green technology that is beneficial to the environment. Biogas technology facilitates the use of animal and plant waste such as cow dung and water hyacinth plants. This study aims to optimize biogas production to achieve optimal biogas volume. Anaerobic Fermentation produces biogas for 21 days. Response Surface Methodology (RSM) with a Central Composite Design (CCD) matrix is ​​used for this optimization. To find the ideal location, the biogas volume data is entered into Minitab. The error value from the optimization results is then computed to verify this optimum location. The optimized biogas produces a volume of 344 mL with an error value of 1.74% at a composition of 0.6089 kg of water hyacinth and 0.6860 kg of cow dung.